Composite catalyst for degrading SF6 at low temperature as well as preparation method and application of composite catalyst
By using a composite catalyst of cerium phosphate and silicon carbide in the catalyst, the problem of high temperature of catalytic degradation of SF6 is solved, efficient degradation under low temperature conditions is achieved, and energy consumption and environmental pollution are reduced.
Patent Information
- Application Number
- CN202510064110.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-22
AI Technical Summary
In the prior art, the temperature of catalytic degradation of SF6 is high, resulting in an increase in energy consumption and making it difficult to achieve low temperature degradation.
Using cerium phosphate as the active component and silicon carbide as the support, a composite catalyst for degrading SF6 at low temperature was prepared by adjusting the pH value and aging conditions.
Under low temperature conditions of 200-550°C, the composite catalyst showed a high SF6 degradation conversion rate, which could completely convert S element to SO3, reducing the environmental pollution of F-containing products such as HF.
Smart Images

Figure CN119857508A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst materials, and in particular to a composite catalyst for low-temperature degradation of SF6 and a preparation method and application thereof. Background Art
[0002] Sulfur hexafluoride (SF6) is a colorless, odorless, non-toxic and non-flammable gas. It is widely used as an insulating agent in the power and semiconductor industries, especially in switchgear, and has excellent inert stability, maintaining stable conditions and dielectric strength at extremely high temperatures. SF6 is a potent greenhouse gas and has become a major risk factor for the global climate. Since 1978, SF6 emissions have been steadily increasing. The amount of SF6 occurring naturally is almost negligible, and its presence in the atmosphere is mainly caused by human factors. Although its concentration is currently low relative to other greenhouse gases, due to its life cycle of 580-3200 years, its warming potential is estimated to be 23,500 times that of carbon dioxide. Therefore, in recent years, multidisciplinary solutions to the SF6 problem have emerged, among which the catalytic degradation of SF6 method has achieved good degradation results.
[0003] Research results in recent years have shown that there are three main types of catalysts for degrading SF6: (1) supported metal catalysts; (2) metal oxides and zeolites; (3) chlorides, phosphates and transition metal complexes, etc. For example, the Chinese invention patent document with publication number CN116078416A discloses a manganese-based catalytic material for degrading sulfur hexafluoride in an air atmosphere. The manganese-based catalytic material uses metal manganese as the active site center and one or more of silicon carbide, silicon dioxide, rectorite, mullite and hydrotalcite as carriers. The manganese-based catalytic material is obtained by physical mixing. The manganese-based catalytic material can be used to catalytically degrade sulfur hexafluoride in an air atmosphere, but the temperature (600°C) for catalytic degradation of SF6 is relatively high, which is not conducive to energy conservation. Summary of the invention
[0004] The technical problem to be solved by the present invention is how to reduce the temperature of catalytic degradation of SF6.
[0005] The present invention solves the above technical problems through the following technical means:
[0006] The first aspect of the present invention provides a composite catalyst for low-temperature degradation of SF6, which uses cerium phosphate as an active component and silicon carbide as a carrier. The active component is dispersed on the carrier, and the cerium phosphate accounts for 23-67wt% of the mass of the composite catalyst.
[0007] Beneficial effects: The present invention uses cerium phosphate as an active component, and the degradation of SF6 shows the best decomposition efficiency and the S element can be completely converted into SO3. Cerium phosphate has an uneven electron distribution and can promote the absorption of SF6 on the positively charged active sites. Silicon carbide has excellent thermal conductivity and is used as a carrier of the catalyst. It is also an ideal n-type semiconductor in a heterogeneous structure. It has negatively charged active sites, which is beneficial to the adsorption of sulfur hexafluoride and can reduce SF6 on the surface of silicon carbide. On the other hand, silicon carbide can promote the precipitation of F in SF6 and reduce the secondary pollution of the environment by F-containing products such as HF obtained in the degradation process. The composite catalyst for low-temperature degradation of SF6 of the present invention has a high SF6 degradation conversion rate at low temperatures.
[0008] The second aspect of the present invention provides a method for preparing the above-mentioned composite catalyst for low-temperature degradation of SF6, comprising the following steps: adding silicon carbide to a cerium precursor, adjusting the pH value to allow the cerium precursor to fully react, and then aging, washing, filtering, drying and calcining to obtain the composite catalyst for low-temperature degradation of SF6.
[0009] Beneficial effects: The present invention couples silicon carbide with a cerium precursor and then obtains a composite catalyst for low-temperature degradation of SF6 through a series of steps. Silicon carbide can strongly interact with cerium phosphate to promote the adsorption and degradation of SF6 on the catalyst surface, so that the catalyst has a higher SF6 degradation activity at low temperatures.
[0010] Preferably, the cerium precursor is one of cerium nitrate hexahydrate or cerium nitrate tetrahydrate, or a mixture of the two.
[0011] Preferably, the solvent of the cerium precursor is phosphoric acid, and the molar ratio of the phosphoric acid to the cerium precursor is 1:1.
[0012] Preferably, the pH value is 9-12.
[0013] Preferably, the aging temperature is 30° C. and the aging time is 24-72 hours.
[0014] Preferably, the drying is carried out in an air atmosphere at a drying temperature of 60-100°C.
[0015] Preferably, the calcination is carried out in an air atmosphere at a calcination temperature of 500-800°C.
[0016] The third aspect of the present invention provides the use of the composite catalyst for low-temperature degradation of SF6 or the composite catalyst for low-temperature degradation of SF6 prepared by the preparation method of the composite catalyst for low-temperature degradation of SF6 described in claims 2-8 to degrade SF6 at low temperature, and the degradation temperature is 200-550°C.
[0017] Beneficial effects: The composite catalyst for low-temperature degradation of SF6 of the present invention can degrade SF6 at 200-550°C and has a high conversion rate of degradation of SF6.
[0018] Preferably, the reaction gas includes nitrogen, oxygen, water vapor and SF6, wherein nitrogen is used as a carrier and the concentration of SF6 is 1 vol%. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic diagram of a reaction device for degrading SF6;
[0020] Figure 2 It is a curve diagram of the catalyst degradation rate and degradation temperature of Examples 1-5 and Comparative Examples 1-5. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0023] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0024] Example 1
[0025] The present embodiment provides a composite catalyst for low-temperature degradation of SF6 and a preparation method, which specifically includes the following steps: dissolving cerium nitrate hexahydrate (2.31 g, 5.32 mmol) in phosphoric acid and mixing evenly to obtain a solution, wherein the molar ratio of phosphoric acid to cerium nitrate hexahydrate is 1:1, adding 4 g of silicon carbide to the above solution, and dripping concentrated ammonia water until the pH value reaches 10, after fully stirring for 1 hour, aging at 30°C for 48 hours under normal pressure air atmosphere, then washing and filtering the aged precipitate, the washing liquid is ethanol, the washing number is 5 times, and then drying it at 60°C in air atmosphere for 24 hours, calcining it at 800°C in air atmosphere for 4 hours to obtain a composite catalyst for low-temperature degradation of SF6, wherein the cerium phosphate in the composite catalyst accounts for 23.8wt% of the mass of the composite catalyst.
[0026] Example 2
[0027] The present embodiment provides a composite catalyst for low-temperature degradation of SF6 and a preparation method, which specifically comprises the following steps: dissolving cerium nitrate hexahydrate (2.31 g, 5.32 mmol) in phosphoric acid and mixing evenly to obtain a solution, wherein the molar ratio of phosphoric acid to cerium nitrate hexahydrate is 1:1, adding 2 g of silicon carbide to the above solution, and dripping concentrated ammonia water until the pH value reaches 10, stirring sufficiently for 1 hour, aging at 30°C for 48 hours under normal pressure air atmosphere, then washing and filtering the aged precipitate, the washing liquid is ethanol, the washing times are 5 times, and then drying it at 60°C in air atmosphere for 24 hours, and calcining it at 600°C in air atmosphere for 4 hours to obtain a composite catalyst for low-temperature degradation of SF6, wherein the cerium phosphate in the composite catalyst accounts for 38.5wt% of the mass of the composite catalyst.
[0028] Example 3
[0029] The present embodiment provides a composite catalyst for low-temperature degradation of SF6 and a preparation method, which specifically comprises the following steps: dissolving cerium nitrate hexahydrate (4.62 g, 10.64 mmol) in phosphoric acid and mixing evenly to obtain a solution, wherein the molar ratio of phosphoric acid to cerium nitrate hexahydrate is 1:1, adding 2 g of silicon carbide to the above solution, and dripping concentrated ammonia water until the pH value reaches 12, stirring sufficiently for 3 hours, aging at 30°C for 48 hours under normal pressure air atmosphere, then washing and filtering the aged precipitate, the washing liquid is ethanol, the washing times are 5 times, and then drying it at 60°C in air atmosphere for 24 hours, and calcining it at 600°C in air atmosphere for 4 hours to obtain a composite catalyst for low-temperature degradation of SF6, wherein the cerium phosphate in the composite catalyst accounts for 55.6wt% of the mass of the composite catalyst.
[0030] Example 4
[0031] The present embodiment provides a composite catalyst for low-temperature degradation of SF6 and a preparation method, which specifically comprises the following steps: dissolving cerium nitrate tetrahydrate (4.62 g, 10.64 mmol) in phosphoric acid and mixing evenly to obtain a solution, wherein the molar ratio of phosphoric acid to cerium nitrate hexahydrate is 1:1, adding 2 g of silicon carbide to the above solution, and dripping concentrated ammonia water until the pH value reaches 12, stirring sufficiently for 3 hours, aging at 30°C for 48 hours under normal pressure air atmosphere, then washing and filtering the aged precipitate, the washing liquid is ethanol, the washing times are 5 times, and then drying it at 60°C in air atmosphere for 24 hours, and calcining it at 600°C in air atmosphere for 4 hours to obtain a composite catalyst for low-temperature degradation of SF6, wherein the cerium phosphate in the composite catalyst accounts for 55.6wt% of the mass of the composite catalyst.
[0032] Example 5
[0033] The present embodiment provides a composite catalyst for low-temperature degradation of SF6 and a preparation method, which specifically comprises the following steps: dissolving cerium nitrate hexahydrate (4.62 g, 10.64 mmol) in phosphoric acid and mixing evenly to obtain a solution, wherein the molar ratio of phosphoric acid to cerium nitrate hexahydrate is 1:1, adding 1.2 g of silicon carbide to the above solution, and dripping concentrated ammonia water until the pH value reaches 12, stirring sufficiently for 3 hours, aging at 30°C for 48 hours under normal pressure air atmosphere, then washing and filtering the aged precipitate, the washing liquid is ethanol, the washing times are 5 times, and then drying it at 60°C in air atmosphere for 24 hours, and calcining it at 600°C in air atmosphere for 4 hours to obtain a composite catalyst for low-temperature degradation of SF6, wherein the cerium phosphate in the composite catalyst accounts for 67.6wt% of the mass of the composite catalyst.
[0034] Comparative Example 1
[0035] Cerium nitrate hexahydrate (4.62 g, 10.64 mmol) was dissolved in phosphoric acid and mixed evenly to obtain a solution, wherein the molar ratio of phosphoric acid to cerium nitrate hexahydrate was 1:1. Concentrated ammonia water was dripped into the above solution until the pH value reached 10. After being fully stirred for 1 hour, it was aged at 30°C for 48 hours under normal pressure air atmosphere. The aged precipitate was then washed and filtered with ethanol as the washing liquid. The washing times were 5 times. After that, it was dried at 60°C in air atmosphere for 24 hours and calcined at 800°C in air atmosphere for 4 hours to obtain a cerium phosphate catalyst.
[0036] Comparative Example 2
[0037] Cerium nitrate hexahydrate (4.62 g, 10.64 mmol) was dissolved in phosphoric acid and mixed evenly to obtain a solution, wherein the molar ratio of phosphoric acid to cerium nitrate hexahydrate was 1:1, concentrated ammonia water was dripped into the above solution until the pH value reached 10, and after being fully stirred for 1 hour, it was aged at 30°C for 48 hours under normal pressure air atmosphere, and then the aged precipitate was washed and filtered, the washing liquid was ethanol, and the washing times were 5 times, and then it was dried at 60°C in air atmosphere for 24 hours, and calcined at 800°C in air atmosphere for 4 hours to obtain a cerium phosphate catalyst; the cerium phosphate catalyst was mechanically mixed with silicon carbide to obtain a composite catalyst, and the mass of the cerium phosphate catalyst in the composite catalyst accounted for 50wt% of the composite catalyst.
[0038] Comparative Example 3
[0039] Cerium nitrate hexahydrate (4.62 g, 10.64 mmol) was dissolved in deionized water, and 2 g of silicon carbide was added, and concentrated ammonia water was dropped until the pH value reached 10. After being fully stirred for 1 hour, it was aged at 30°C for 48 hours under normal pressure air atmosphere. The aged precipitate was then washed and filtered with ethanol as the washing liquid, and the washing times were 5 times. After that, it was dried at 60°C in air atmosphere for 24 hours, and calcined at 800°C in air atmosphere for 4 hours to obtain CeO2-SiC catalyst, in which the mass of CeO2 accounted for 47.8wt% of the catalyst.
[0040] Comparative Example 4
[0041] Lanthanum nitrate hexahydrate (4.86 g, 11.22 mmol) was dissolved in phosphoric acid and mixed evenly to obtain a solution, wherein the molar ratio of phosphoric acid to cerium nitrate hexahydrate was 1:1, 2 g of silicon carbide was added to the above solution, and concentrated ammonia water was dropped until the pH value reached 12. After being fully stirred for 3 hours, the solution was aged at 30°C for 48 hours under normal pressure air atmosphere, and then the aged precipitate was washed and filtered, the washing liquid was ethanol, and the washing times were 5 times. After that, it was dried at 60°C in air atmosphere for 24 hours, and calcined at 600°C in air atmosphere for 4 hours to obtain LaPO4-SiC catalyst, wherein LaPO4 in the composite catalyst accounted for 56.9wt% of the mass of the composite catalyst.
[0042] Comparative Example 5
[0043] Praseodymium nitrate hexahydrate (4.63 g, 10.65 mmol) was dissolved in phosphoric acid and mixed evenly to obtain a solution, wherein the molar ratio of phosphoric acid to cerium nitrate hexahydrate was 1:1. 2 g of silicon carbide was added to the above solution, and concentrated ammonia water was dripped until the pH value reached 12. After being fully stirred for 3 hours, the solution was aged at 30°C for 48 hours under normal pressure air atmosphere. The aged precipitate was then washed and filtered with ethanol as the washing liquid. The washing times were 5 times. After that, the solution was dried at 60°C in air atmosphere for 24 hours and calcined at 600°C in air atmosphere for 4 hours to obtain PrPO4-SiC catalyst. In the composite catalyst, PrPO4 accounted for 55.6 wt% of the mass of the composite catalyst.
[0044] Experimental example
[0045] The SF6 catalytic degradation reaction in the present invention is divided into two important pathways: (1) hydrolysis reaction and (2) oxidation reaction. The schematic diagram of the SF6 catalytic degradation reaction device is shown in FIG. Figure 1As shown. The reaction gas is passed through the gas distribution system to mix SF6, N2, O2 and water vapor in a mixed ratio, wherein N2 is the carrier gas, the concentration of SF6 is 1vol%, the concentration of O2 is 10vol%, and the concentration of water vapor is 5vol%. After the gas is evenly mixed, it is passed into a fixed bed reactor with a certain amount of catalyst placed. The temperature controller controls the temperature range. The catalyst performance test temperature is 200-800℃. The tested gas is cooled with ice water and adsorbed with NaOH before passing into a gas chromatograph to detect the SF6 content in the reactor; then, before the catalyst performance test, the SF6 content in the initial reaction gas is tested through an empty bypass. The SF6 degradation rate per gram of catalyst in the catalyst is calculated by the SF6 content before and after the reaction, and the catalyst performance results are obtained as shown in Figure 2 shown.
[0046] from Figure 2 It can be seen that the composite catalysts for low-temperature degradation of SF6 in Examples 1-5 have better SF6 catalytic degradation activity at 200-550°C. Compared with Comparative Example 1, the cerium phosphate catalyst of Comparative Example 1 obtained by the same method has a higher conversion rate at a temperature of 200-550°C. The SF6 catalytic degradation rate of the composite catalyst for low-temperature degradation of SF6 at a low temperature of 400°C can reach 70%, while that of the cerium phosphate catalyst of Comparative Example 1 is 45%. The composite catalyst for low-temperature degradation of SF6 has a good development prospect.
[0047] from Figure 2 It can be seen that compared with Example 2, although both Example 1 and Comparative Example 2 use silicon carbide as a carrier, it is obvious that the composite catalyst obtained by adding silicon carbide to the cerium precursor has better SF6 catalytic degradation activity at low temperatures. This is because silicon carbide and the cerium precursor are coupled during the preparation process, and after the subsequent series of preparation steps, silicon carbide and cerium phosphate have a strong interaction, which promotes the adsorption and degradation of SF6 on the catalyst.
[0048] from Figure 2 It can be seen that, compared with Comparative Example 3, the cerium nitrate active component of Example 1 has higher SF6 catalytic degradation activity than the cerium oxide active component. Compared with Comparative Examples 4 and 5, the cerium phosphate active component of Example 1 has better SF6 catalytic degradation activity than lanthanum phosphate and praseodymium phosphate.
[0049] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite catalyst for low temperature degradation of SF6, characterized in that: The method uses cerium phosphate as an active component and silicon carbide as a carrier. The active component is dispersed on the carrier, and the cerium phosphate accounts for 23-67wt% of the mass of the composite catalyst.
2. The method for preparing a composite catalyst for low-temperature degradation of SF6 according to claim 1, characterized in that: The following steps are involved: Silicon carbide is added to a cerium precursor, and the pH value is adjusted to allow the cerium precursor to fully react. The composite catalyst for low-temperature degradation of SF6 is obtained after aging, washing, filtering, drying and calcination.
3. The method for preparing a composite catalyst for low-temperature degradation of SF6 according to claim 2, characterized in that: The cerium precursor is one of hexahydrated cerium nitrate and tetrahydrated cerium nitrate, or a mixture of the two.
4. The method for preparing a composite catalyst for low-temperature degradation of SF6 according to claim 2, characterized in that: The solvent of the cerium precursor is phosphoric acid, and the molar ratio of the phosphoric acid to the cerium precursor is 1:
1.
5. The method for preparing a composite catalyst for low-temperature degradation of SF6 according to claim 2, characterized in that: The pH value is 9-12.
6. The method for preparing a composite catalyst for low-temperature degradation of SF6 according to claim 2, characterized in that: The aging temperature is 30° C., and the aging time is 24-72 hours.
7. The method for preparing a composite catalyst for low-temperature degradation of SF6 according to claim 2, characterized in that: The drying is carried out in an air atmosphere at a drying temperature of 60-100°C.
8. The method for preparing a composite catalyst for low-temperature degradation of SF6 according to claim 2, characterized in that: The calcination is carried out in an air atmosphere at a temperature of 500-800°C.
9. Use of the composite catalyst for low-temperature degradation of SF6 as claimed in claim 1 or the composite catalyst for low-temperature degradation of SF6 as claimed in claims 2-8 to prepare the composite catalyst for low-temperature degradation of SF6 in low-temperature degradation of SF6, characterized in that: The degradation temperature is 200-550℃.
10. The use of degrading SF6 at low temperature according to claim 9, characterized in that: The reaction gas includes nitrogen, oxygen, water vapor and SF6, wherein nitrogen is used as a carrier and the concentration of SF6 is 1 vol%.
Citation Information
Patent Citations
Catalytic material based on elemental manganese for degrading sulfur hexafluoride in air atmosphere
CN116078416A